The Effects of Land Tenure Policy on the Environment in the Gambella Region - Kompuok, Chuol (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
An attempt is made to investigate the consequences of land tenure policy on the environment enhancing reforestation as a means of ascertaining tenure security in the Gambella region. This paper sheds light on the accelerated pace of deforestation in the study area and its impact on the environment. The theoretical and conceptual issues of the interrelation between reforestation, deforestation, land tenure system, and other socio-economic indicators have been given due attention in the literature review. Research methodology gives much focus on qualitative data analysis that uses ranges of data collection approaches; FGD, KII, semi-structured household interviews with the inclusion of secondary data reviews. The paper considers the effect of land tenure system on the environment and discusses the landholding system in the study area, including customary land rights among the Nuer, the Anywaa, and the Majangir. To this effect, external factors and urban expansions are addressed with the view to understanding the impact of socio-cultural practice on physical environment perception and management. A conclusion and policy implications are also discussed.